Penerapan Metode Team Teaching Untuk Meningkatkan Hasil Belajar Siswa Dalam Mata Pelajaran PAI Kelas IX Di SMP Taman Siswa Teluk Betung Bandar Lampung: Penerapan Metode Team Teaching Untuk Meningkatkan Hasil Belajar (An Naba, 2020)
The main necessity in one's life is education. Education is a very important factor in human life. Team teaching is basically a learning method carried out by two or more teachers who collaborate in teaching groups of students which are carried out jointly by several teachers. The team or teachers who present the lesson material with the team teaching method presents the same lesson material in the same time and purpose. The type of this research is the classroom action research. The subjects were class IX A students at Taman SiswaTelukBetung Middle School in Bandar Lampung, with a total of 35 students. The data collection techniques in this research used observation, learning outcomes tests, and documentation. This research consisted of two cycles with two meetings in each cycle. The data analysis techniques were using qualitative descriptive analysis. The research success criteria set for student learning outcomes are ≥ 80 reaching 80% based on KKM in schools. The results showed that the application of team teaching learning methods could improve the learning outcomes of class IX A students at Taman SiswaTelukBetung Middle School, Bandar Lampung. The number of students who have completed their study in the first cycle is 18 people or equivalent to 51%. In the second cycle, the number of students who completed study was 31 students or equivalent to 88%.